MEASURING STUDENT’S DIFFICULTIES IN READING COMPREHENSION IN LOWER SECONDARY LEVEL - Adawiyah Adha Asri Rais; Muhammad Sofian Hadi; Mutiarani (Getsempena English Education Journal, 2021)
The aim of this study was to prove the ability of students’ comprehension in measuring their difficulties of reading comprehension in junior high school level. This study was conducted towards students’ difficulties related to types of questions of reading comprehension. After analyzing the data from the test, the researchers concluded that the study in MTs 1 Muhammadiyah Ciputat had problems in reading comprehension. There are five sorts of the categories as difficult questions in reading comprehension. They are primary thought, making induction, finding reference, vocabulary, and detail data. The results of study revealed that students’ difficulties in answering reading questions were in comprehending main idea of reading (38%), finding reference (52%), making inference (52%), vocabulary (79%), and detail information (77%). The researchers also measured the level of difficulty in reading comprehension to figure out the students’ ability in comprehending the English text. As a result, most of the students had difficulty in determining the main idea.